Variations of ethnic boundary significance in north Norway - Thuen, Trond (Polar Record, 2012)
In coastal north Norway the Saami people have lived in a close relationship with Norwegians or Norse people for a thousand years or more. This relationship has been articulated in various ways over the centuries, and this article argues that in parts of the region it took a rather intimate form based on the shared exploitation of the dominant marine and terrestrial niches, a common class position as tenant farmers, a varying practice of inter-ethnic marital relations and the effects of a bilateral kinship system. Various forms of inter-ethnic contact and exchange may thus have served to reduce the relevance of ethnic difference in daily life, as suggested by Barth's argument about the integrative effect of transactions, but contrary to his argument about the transactional reinforcement of ethnic boundaries. Contrary to the intention, governmental assimilatory efforts served to reproduce the boundary as the basis for a ranked society and left coastal Saami individuals in some confusion as to how to define themselves, often opting for a mixed category of Norwegian and Saami, labelled ‘Northerner’. Ethno-political emancipation in recent years has tended to put pressure on this identity construction and promoted a dichotomised identity as either Saami or Norwegian.